Artificial Intelligence in Indonesian Elementary Education: A Systematic Review of Student Motivation, Engagement, and Implementation Challenges - Afif Alfiyanto; Fitri Hidayati; Muhammad Ghazali; Ivan Riyadi (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
Artificial intelligence (AI) is increasingly used in elementary education to support personalized, multimodal, inclusive, and emotionally responsive learning. However, evidence on its contribution to students’ motivation and engagement in Indonesian elementary schools remains limited and fragmented. This systematic literature review synthesized eight Indonesian studies published between January 2020 and April 2026, selected through PRISMA 2020 procedures from Scopus, ERIC, Web of Science, Google Scholar, and relevant national peer-reviewed journals. Using thematic narrative synthesis, the review found that AI-supported learning may enhance students’ behavioral, emotional, and cognitive engagement through interactive inquiry, culturally relevant multimedia, emotional learning support, adaptive scaffolding, and inclusive access. AI-based mobile applications, AI-generated animation, AI-driven Canva tools, digital counseling platforms, AI game-based literacy models, and AI-assistive technologies were reported to strengthen participation, enjoyment, learning interest, comfort, comprehension, and accessibility. However, the evidence remains small, methodologically diverse, and inconsistent in measuring motivation and engagement. The findings indicate that AI should be positioned as a pedagogical support rather than a teacher substitute, requiring teacher readiness, ethical governance, inclusive design, infrastructure support, and contextual alignment with Indonesian elementary classrooms.